PSIXOLOGIK MANBALARDA PROFESSOR-O‘QITUVCHILAR KASBIY RIVOJLANISHIDA O‘Z-O‘ZINI BOSHQARISH MASALALARINING YORITILISHI - Raximov, B.A. (SCIENCE and SOCIETY, 2024)
This article analyzes psychological theories on the issue of self- regulation in the professional development of lecturers operating in the higher education system, as well as psychological and acmeological factors of self- regulation, and describes opinions and conclusions on the problem under consideration.
Keywords: self-regulation; lecturer; profession; communication; interpersonal relationships; motivation; personality; values; need; self-esteem; professional training